Language Origins Viewed in Spontaneous and Interactive Vocal Rates of Human and Bonobo Infants - Oller, D. Kimbrough; Griebel, Ulrike; Iyer, Suneeti Nathani; Jhang, Yuna; Warlaumont, Anne S.; Dale, Rick; Call, Josep (Frontiers in Psychology, 2019)
From the first months of life, human infants produce “protophones”, speech-like, non-cry sounds, presumed absent or only minimally present in other apes. But there have been no direct quantitative comparisons to support this presumption. In addition, by two months, human infants show sustained face-to-face interaction using protophones, a pattern thought also absent or very limited in other apes, but again, without quantitative comparison. Such comparison should provide evidence relevant to determining foundations of language, since substantially flexible vocalization, the inclination to explore vocalization, and the ability to interact socially by means of vocalization are foundations for language. Here we quantitatively compare data on vocalization rates in three captive bonobo (Pan paniscus) mother-infant pairs with various sources of data from our laboratories on human infant vocalization. Both humans and bonobos produced distress sounds (cries/screams) and laughter. The bonobo infants also produced sounds that were neither screams nor laughs and that showed acoustic similarities to the human protophones. These protophone-like sounds confirm that bonobo infants share with humans the capacity to produce vocalizations that appear foundational for language . Still, there were dramatic differences between the species in both quantity and function of the protophone and protophone-like sounds. The bonobo protophone-like sounds were far less frequent than the human protophones, and the human protophones were far less likely to be interpreted as complaints and more likely as vocal play. Moreover, we found extensive vocal interaction between human infants and mothers, but no vocal interaction in the bonobo mother-infant pairs—while bonobo mothers were physically responsive to their infants, we observed no case of a bonobo mother vocalization directed to her infant. Our cross-species comparison focuses on low- and moderate-arousal circumstances because we reason the roots of language entail vocalization not triggered by excitement, for example, during fighting or intense play. Language appears to be founded in flexible vocalization, used to regulate comfortable social interaction, to share variable affective states at various levels of arousal, and to explore vocalization itself.